2015
DOI: 10.5812/numonthly.29127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Hydrochlorothiazide in Primary Monosymptomatic Nocturnal Enuresis in Boys With Idiopathic Hypercalciuria

Abstract: Background:Idiopathic hypercalciuria (IHC) can be one of the causes of nocturnal enuresis (NE) and hydrochlorothiazide (HCT) ameliorates hypercalciuria.Objectives:The aim of this study was to assess the therapeutic efficacy of HCT in boys with primary monosymptomatic NE (PMNE).Patients and Methods:This study was a randomized double-blind placebo-controlled clinical trial. A hundred boys with PMNE and IHC were randomly assigned into two groups of experimental (treated with HCT 1 mg/kg/day) and control and all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Some groups have found increased prevalence of hypercalciuria in enuretic children and some have not . The few therapeutic studies that have been carried out have been of low quality, and have failed to provide evidence that hypercalciuria in enuretic children needs to be addressed in order to make them dry . Hypercalciuria, if present, is probably an epiphenomenon related to nocturnal polyuria …”
Section: Urine Productionmentioning
confidence: 99%
“…Some groups have found increased prevalence of hypercalciuria in enuretic children and some have not . The few therapeutic studies that have been carried out have been of low quality, and have failed to provide evidence that hypercalciuria in enuretic children needs to be addressed in order to make them dry . Hypercalciuria, if present, is probably an epiphenomenon related to nocturnal polyuria …”
Section: Urine Productionmentioning
confidence: 99%
“…Yousefichaijan et al in a study on the therapeutic effect of HCT on PMNE only in males, compared the case (HCT and conservative treatment) and control (conservative treatment) groups. They concluded that HCT was an effective therapeutic option; hence, it can be prescribed in the treatment of PMNE (17). Jang et al in a study showed that the impact of HCT, which induced hypocalciuria in hypercalciuric rats, was associated with increased expression of transient receptor potential vanilloid 5 (TRPV5) protein; TRPV5 may also have a significant effect on the regulation of calcium excretion from the urinary system (22).…”
Section: Discussionmentioning
confidence: 99%
“…thiazide diuretics are used as drugs that are easy to use, have few complications, are inexpensive, widely available, and acceptable (17). Thiazides induce calcium reabsorption in distal tubules of kidney and ameliorate hypercalciuria (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…(9). Some authors found idiopathic hypercalciuria (IH) to be more common in children with PMNE than in children without nocturnal enuresis and for this reason they assume that IH could be one of the contributing pathophysiologic factor to PMNE (10,11,12). Considering 24 h-variations in urine calcium excretion, the diagnosis of hypercalciuria is most accurately determined from the urine collected for 24 h. This is usually difficult to achieve in children who have nocturnal enuresis.…”
Section: Introductionmentioning
confidence: 99%